Design Calculation Model of Three-Layer Composite Reinforce Concrete Structures - Jan Bujnak; Elena A. Korol; Vasily E. Latushkin (Communications - Scientific letters of the University of Zilina, 2012)
The three-layer structures with a thermal insulation layer of small strength concrete keep the intermediate place between the standard reinforce concrete structures and composite constructions. The calculation model in which the cross-section of three-layer structure is substituted by I-beam homogeneous section of imaginary higher strength concrete is selected. The executed analysis have verified the possibility to use the I-beam transformed section model even for the calculation of three-layer composite reinforce concrete structural elements.